OCT ANGIOGRAPHY AND DOPPLER SONOGRAPHY IN NORMAL-TENSION GLAUCOMA - Lešták, J; Fůs, M; Benda, A; Marešová, K (Ceska a slovenska oftalmologie, 2020)
AIMS: To investigate the dependence of blood vessel density and velocity in ophthalmic artery and arteria centralis retinae of the same eye in patients with normotensive glaucoma. METHODS: The sample consisted of 20 patients with normotensive glaucoma (NTG). There were 17 women (mean age 56.1) and 3 men (mean age 60 years). Inclusion criteria for study: visual acuity 1.0 with correction up to ±3 dioptres, approximately equal changes in the visual field, whereby it was incipient NTG and diagnosis was confirmed by electrophysiological examination, without further ocular or neurological disease. Parameters of vessel density (VD) were evaluated by Avanti RTVue XR (Optovue). Perfusion parameters such as peak systolic velocity (PSV), end diastolic velocity (EDV) and resistive index (RI) were evaluated for ophthalmic artery (AO) and arteria centralis retinae (ACR) using Doppler sonography (Affinity 70G Philips, probe 5-12 MHz). Visual field (VF) was evaluated by automated perimeter (Medmont M700) using fast threshold glaucoma strategy test. The sum of sensitivity levels in apostilb (asb) were evaluated in range 0-22 degrees of visual field. Resulting values of VF were compared with VD and perfusion parameters in AO and ACR at the same eye. RESULTS: Pearsons correlation coefficient was used to evaluate the dependence. Data shows, that changes in visual fields are mainly caused by peripapillary VD of small and all vessels, and vessels throughout measured image area also. Correlation of small vessels throughout measured image area was weak (r = 0.23). Moderate negative correlation was found for PSV in AO and peripapillary small VD (r = -0.46), all peripapillary VD (r = -0.49), VD in whole area (r = -0.45), then between EDV in AO and VD in whole area (r = -0.42). Other correlations between VD and perfusion parameter were insignificant. CONCLUSIONS: Study confirms, that changes of visual field in NTG patients are mainly caused by VD rather than perfusion parameters, especially in AO. Perfusion parameters in ACR are not significantly correlated with changes of VF in NTG patients.
Keywords: normotenzní glaukom; glaukom; vessel density; Intraocular Pressure; Middle Aged; nitrooční tlak; mužské pohlaví; Optic Disk; visual field; Low Tension Glaucoma; Glaucoma; OCT angiography; ženské pohlaví; optická koherentní tomografie; Humans; normotension glaucoma; Tomography, Optical Coherence; Doppler sonography; lidé středního věku; Female; discus nervi optici; lidé; Male